Investigating the role of foreign aid, FDI, and remittance on the public health of selected South Asian countries - Md. Atik Hasan; Shabikunnahar Suborna; Afrida Jinnurain Urbee (Research in Globalization)
Foreign aid, remittance, and foreign direct investment have a significant role in shaping and promoting globalization and these factors also play a vital role in determining health quality in developing countries. Developing countries, especially South Asian countries still need research and policies to efficiently utilize the contributions of these external capital sources in their health sector. For this reason, the present study examined the effects of different globalization-related factors (remittances, foreign direct investment, foreign aid) and health spending from 2000 to 2020 on the quality of healthcare in six South Asian countries: Bangladesh, India, Nepal, Pakistan, Maldives, and Sri Lanka. Moreover, this investigation introduces an unprecedented facet to the realm of health sector research by introducing a novel health quality index that incorporates life expectancy, newborn mortality rate, maternal mortality rate, and illness prevalence (specifically tuberculosis). This study used Augment Mean Group (AMG) estimation for data analysis. To ensure the precision and dependability of the findings, this research utilizes sophisticated statistical methodologies, including the Common Correlated Effect of Mean Group (CCEMG), Driscoll-Kraay Robust Standard Error approaches, and Dumitrescu and Hurlin (D-H) causality test, thereby establishing their dependability. The findings of the study demonstrate that foreign aid and health spending have a significant beneficial impact on the health quality of South Asia. In contrast, remittances tend to harm health quality. Furthermore, the influence of FDI on the quality of health in South Asia is equivocal. South Asian countries must allocate more of their budget to the health sector and ensure that foreign aid is properly utilized for its development. On the other hand, these countries are required to take policy and create an environment that will help to improve health quality through effective use of remittance and FDI.